2007
DOI: 10.1002/jso.20714
|View full text |Cite
|
Sign up to set email alerts
|

Retropubic versus perineal radical prostatectomy in early prostate cancer: Eight‐year experience

Abstract: Radical perineal prostatectomy is an excellent alternative approach for radical surgery in the treatment of early prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 45 publications
1
20
0
Order By: Relevance
“…The systematic reviews suggested some problems with the reliability of the observational evidence and in some cases the methods of synthesis do not appear to be robust. Of the three RCTs, only the trial reported by Martis and colleagues 114 provided longer-term outcome data (biochemical recurrence); the others focussed on perioperative outcomes. 115,116 The time to biochemical recurrence survival curves reported for PRP and RRP in Martis and colleagues 114 are almost identical, hence we assumed no difference in biochemical recurrence-free survival between the two procedures.…”
Section: Case Study 1: Full Guideline Model For Prostate Cancermentioning
confidence: 99%
“…The systematic reviews suggested some problems with the reliability of the observational evidence and in some cases the methods of synthesis do not appear to be robust. Of the three RCTs, only the trial reported by Martis and colleagues 114 provided longer-term outcome data (biochemical recurrence); the others focussed on perioperative outcomes. 115,116 The time to biochemical recurrence survival curves reported for PRP and RRP in Martis and colleagues 114 are almost identical, hence we assumed no difference in biochemical recurrence-free survival between the two procedures.…”
Section: Case Study 1: Full Guideline Model For Prostate Cancermentioning
confidence: 99%
“…Prostate cancer is the most common malignancy and the second leading cause of cancer death in men (1). Active treatment is usually recommended for patients with localized disease and a long life expectancy, with radical prostatectomy (RP) being shown to be superior to other treatments in appropriate patients.…”
Section: Introductionmentioning
confidence: 99%
“…Active treatment is usually recommended for patients with localized disease and a long life expectancy, with radical prostatectomy (RP) being shown to be superior to other treatments in appropriate patients. Because the urologists always seek less invasive and less morbid therapeutic options and the financial sources supplying health worldwide tend Clinical Urolo�y Clinical Urolo�y doi: 10.1590/S1677-55382010000600007 to support therapeutic modalities resulting in shorter hospitalization and early recovery, interest in radical perineal prostatectomy (RPP) has increased again in recent years (1,2). When compared to radical retropubic prostatectomy (RRP), laparoscopic or roboticassisted procedures have advantageous outcome data regarding duration of hospitalization, loss of blood, time needed to recover from the disease, and return to normal daily life (3).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations